2008
DOI: 10.1097/brs.0b013e31817e6974
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study on Interaction Between Human Nucleus Pulposus Cells and Mesenchymal Stem Cells Through Paracrine Stimulation

Abstract: The results showed a possible mechanism of interaction between MSCs and NP cells mediated by secreted factors. The most significant effect on NP cells was enhancement of cellular proliferation when they were cocultured with even a small number of MSCs. To differentiate MSCs into NP-like cells with heightened collagen II expression, MSCs must be in an environment containing numerous NP cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 51 publications
6
64
0
Order By: Relevance
“…Other researchers have also reported on the stimulatory effect of human NP cells with co-culture with MSCs. Yang et al (2008) showed an increase in cell proliferation, while Le Visage et al (2006) reported an increase in GAG production in a pellet co-culture system. Furthermore, Vadalà et al (2008) showed increased NP cell gene expression of collagen II after cell-matrix-cell co-culture with MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also reported on the stimulatory effect of human NP cells with co-culture with MSCs. Yang et al (2008) showed an increase in cell proliferation, while Le Visage et al (2006) reported an increase in GAG production in a pellet co-culture system. Furthermore, Vadalà et al (2008) showed increased NP cell gene expression of collagen II after cell-matrix-cell co-culture with MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of mRNA of the NP marker genes COL2A1, COL6A2, ACAN and SOX9 has been reported as the main result of direct co-culture of human NPCs and MSCs (6). Indirect co-culturing of NPCs and MSCs in the insert system promoted COL2A1 expression in the MSCs and the proliferation of NPCs as well as the expression of ACAN (7). A study of human MSCs that were co-cultured with NP revealed higher expression of COL2A1 and ACAN (8).…”
Section: Introductionmentioning
confidence: 99%
“…Co-culture of MSC with NP cells stimulates both NP cells proliferation and MSC differentiation toward the chondrogenic lineage. (200)(201)(202)(203) Increased production of cytokines, particularly TGF-b favors these transformations. (203)(204)(205) The NP contains MSC that are similar to the MSC recovered from bone marrow (206), and studies in animal models of DD have shown that MSC injected in the NP area not only survive for months but also proliferate in canine (207,208), porcine (209), and rabbit models (210).…”
Section: Lbp Pathophysiologymentioning
confidence: 99%